Rancangan sistem pengukuran kinerja untuk penentuan key performance indicator dengan metode Balance scorecard - Lucky Setiawan; Yuliani Fauziah (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
This research adopts the Vision and Mission of a textile company headquartered in Tangerang. This company produces producing polo shirts, golf shirts, track suits, sweat shirts, and pants using materials such as single jersey, pique, lace in cotton, polyester, and others. The company's vision and mission can represent other textile companies that have the same processes and products. The characteristics of textile companies that have processes with human skill factors become critical points that are difficult to replace with robot technology. This has an impact on the needs of a large number of human resources in the industry. The increase in labor costs which always increases every year has a very significant impact on production costs. Thus, expansion is one of the critical factors to be used as a top management strategy in determining the current KPI items. The Balanced Scorecard is a performance evaluation method that can meet these expectations. The design of company performance measurement in this study begins with the translation of the company's vision and mission, secondly, making a proposed corporate strategy using the PQCDSME approach (profit, quality, Cost, Delivery, Service, Moral, Environment). Third, calcify the company's strategy into the perspective of the balanced scorecard. Fourth, the decision making process to determine KPI items using the brainstorming method. Fifth, determining the critical success factor and key performance indicator. Other factors are also compared between the achievement of the previous year as an illustration of determining a target. So the target given will be in accordance with the SMART rules (speciefic, measurable, achievable, realistic and timely). The results are obtained with 4 criteria (financial, consumer, internal business processes, learning and growth). This performance measurement produced 19 key performance indicators, consisting of 6 financial perspective indicators, 1 customer perspective indicator, 7 internal business process perspective indicators, and 5 growth and learning perspective indicators.